Computing Individual Risks Based on Family History in Genetic Disease in the Presence of Competing Risks. (9th November 2017) - Nuel, Gregory; Lefebvre, Alexandra; Bouaziz, Olivier
Abstract : When considering a genetic disease with variable age at onset (e.g., familial amyloid neuropathy, cancers), computing the individual risk of the disease based on family history (FH) is of critical interest for both clinicians and patients. Such a risk is very challenging to compute because 1 the genotype X of the individual of interest is in general unknown, 2 the posterior distribution P X ∣ F H, T > t changes with t (T is the age at disease onset for the targeted individual), and 3 the competing risk of death is not negligible. In this work, we present modeling of this problem using a Bayesian network mixed with (right-censored) survival outcomes where hazard rates only depend on the genotype of each individual. We explain how belief propagation can be used to obtain posterior distribution of genotypes given the FH and how to obtain a time-dependent posterior hazard rate for any individual in the pedigree. Finally, we use this posterior hazard rate to compute individual risk, with or without the competing risk of death. Our method is illustrated using the Claus-Easton model for breast cancer. The competing risk of death is derived from the national French registry.